Tribological Behavior of Reinforced PTFE Composites and Un-Reinforced Polyketone-Based Materials against Coated Steel - Federica Amenta; Giovanni Bolelli; Stefano De Lorenzis; Alessandro Bertarini; Luca Lusvarghi (Lubricants, 2021)
In this study, two polymeric materials were tested in a dry rotating “pin-on-disc” configuration against differently coated surfaces, to evaluate their tribological response under conditions, such as those of rotary lip seals, and to identify the wear mechanism of each coupling. A PTFE based material, reinforced with glass fibers and a solid lubricant, and unreinforced polyketone were tested against a chromium oxide coating deposited by plasma thermal spraying, a CrN/NbN superlattice coating deposited by Physical Vapor Deposition (PVD), and a Diamond-Like Carbon (DLC) coating obtained through a hybrid PVD/PECVD (Plasma-Enhanced Chemical Vapor Deposition) process. The PTFE matrix composite offers better overall performance, in terms of specific wear rates and friction coefficients than polyketone. Although the tribological behavior of this material is generally worse than that of the PTFE matrix composite, it can be used without reinforcing fillers. Our analysis demonstrates the importance of transfer-film formation on the counter-surfaces, which can prevent further wear of the polymer if it adheres well to the counterpart. However, the tribofilm has opposing effects on the friction coefficient for the two materials: its formation leads to lower friction for PTFE and higher friction for polyketone.